Request Strategies by Sundanese In Same and Cross Gender Communication - Febri Dwi Putra (Passage, 2019)
This study investigates the patterns of request strategies used by Sundanese males and females when communicating with the same and cross-gender. It also explores the possible factors affecting the use of request by the participants. Applying a descriptive qualitative method, the participants for this research were 5 Sundanese females and 5 Sundanese males, aged 19-23. The participants were students from a public university in northern Bandung which were purposely selected. To analyze the data, this study employed request strategies theory proposed by Blum-kulka and Olshtain (1984) and factors affecting the request strategies by Brown and Levinson (1987) and Han (2013). The results show that Sundanese males and females used direct strategy more than conventionally indirect and non-conventionally indirect strategy. Sundanese people use direct strategy when requesting to friends both to same and cross-gender, while conventionally indirect strategy used to request to strangers. These findings suggest that the gender of the interlocutors is not taken into consideration for determining the request strategy, but the speakers pay attention more to age and the distance with the interlocutors. This is due to cultural characteristics of Sundanese that applies undak usuk basa. Keywords: speech act of request, request strategies, gender, Sundanese